DEVELOPING A SOFTWARE FOR FUZZY GROUP DECISION SUPPORT SYSTEM: A CASE STUDY - (:unkn) unknown (TURKISH ONLINE JOURNAL EDUCATIONAL TECH-TOJET, 2009)
The complex nature and uncertain information in social problems required the emergence of fuzzy decision support systems in social areas. In this paper, we developed user-friendly Fuzzy Group Decision Support Systems (FGDSS) software. The software can be used for multi-purpose decision making processes. It helps the users determine the main and sub evaluation criteria, their weights, and evaluate the performance according to the number of decision makers and evaluation weights of criteria. It also allows the user to use two different fuzzy inference methods. In the fuzzyfication unit, universe of discourse is made up of three different membership functions. The software, which has four main screens, is developed by using Delphi programming language and is used for the purpose of performance assessment of research assistants at Marmara University, Technical Education Faculty.
Keywords: Fuzzy logic; Multi-criteria decision making; Performance evaluation